Ilmu Ladunni dalam Perspektif al-Ghazali - Sutiyono, Agus (Nadwa, 2013)
Science Ladunni inspiration is flowing light, which can occur after improvement (taswiyah). Rationally, all knowledge can be acquired through learning. This is key in pursuing the events and education trips. Learning becomes important when one wants to reach the succes top life in understanding the science. How to get the science ladunni according to al-Ghazali, namely; first, trying to grab all the knowledge and take the highest ration of science the most. Second, proper training (ar-riyad ash sad iqah) and supervision are valid (al-muraqabah as sahihah), and still a fraid God with truth. Third, thinking (tafakur), if the soul has learned and trained to be a science, then he bertafakur. Fourth rabbaniyah purify hearts decorated with zikrullah.